The future of the university? The voice of young Polish scholars - Anna M. Kola; Krzysztof Leja (Gdańsk University of Technology, Faculty of Management and Economics, 2016)
Changes of universities should not be a result of administrators' and university managers' decisions (as a top-down approach), but of initiatives from the academic community. It is a kind of third way, which goes beyond the liberal discourse of the capitalist, who want to turn universities into companies, but it is not only the realization of the vision of the university officials. Taking into account our research and educational experience, we would like to introduce a wider perspective on the role of the contemporary university – regarding the core-periphery position of universities in a global world. In addition, our aim is to show how strategies of resistance can be built, which will result in effective and sustainable conversion of thinking about the university as an institution in shaping and creating an elite, as well as developing mechanisms of pro-quality, taking into account social factors. To reveal this way of thinking and show possibilities of taking action, we describe the main Polish initiatives that can change the university world in every field. An example of such a social movement is Citizens of Academia (Obywatele Nauki). Its members are young (usually post-doctoral), as well as more experienced scholars, who, despite the fact of achieving scientific and academic success, are working for the common good and the good of the university seen as an important social institution. The university ought to be an institution responsible for the process of social and cultural development.We agree that research on the role and activity of the movement is important to understand the direction of changes of the (post)modern university and society. The goal of such ethnographically inspired research is diagnosis of a specific engaged academic community. The article will present conclusions of the pilot study, conducted among the founders and initiators of the ON movement. Additional important objectives of the paper are to provide practical recommendations for policymakers, academic communities, research institutions and university administration, as well as answers to the question about possibilities of using the intellectual potential of young, talented, rebel and open scholars, to became a catalyst for desired change of the university, as well as development of personal careers of Polish academicians
Keywords: I23; 330; contemporary university; social movements; Citizens of Academia